2016
DOI: 10.1186/s13568-016-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ustR and the Golgi protease KexB are required for ustiloxin B biosynthesis in Aspergillus oryzae

Abstract: Ustiloxin B, originally isolated from the fungus Ustilaginoidea virens, is a known inhibitor of microtubule assembly. Ustiloxin B is also produced by Aspergillus flavus and is synthesized through the ribosomal peptide synthesis pathway. In A. flavus, the gene cluster associated with ustiloxin B production contains 15 genes including those encoding a fungal C6-type transcription factor and ustiloxin B precursor. Although the koji mold Aspergillus oryzae, which is genetically close to A. flavus, has the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…It is very interesting to note that, e.g., ustiloxin B and ustilaginoidin C, have both been isolated from the rice false smut pathogen Villosiclava virens (= Ustilaginoidea virens ) even though they are not biosynthetically related. However, these two types of secondary metabolites have also been found in Aspergillus flavus (Umemura et al 2014 ; Tsukui et al 2015 ; Yoshimi et al 2016 ). This is remarkable as both unrelated fungi occur on rice.…”
Section: Secondary Metabolite Potentialmentioning
confidence: 99%
“…It is very interesting to note that, e.g., ustiloxin B and ustilaginoidin C, have both been isolated from the rice false smut pathogen Villosiclava virens (= Ustilaginoidea virens ) even though they are not biosynthetically related. However, these two types of secondary metabolites have also been found in Aspergillus flavus (Umemura et al 2014 ; Tsukui et al 2015 ; Yoshimi et al 2016 ). This is remarkable as both unrelated fungi occur on rice.…”
Section: Secondary Metabolite Potentialmentioning
confidence: 99%
“…Each repeat is flanked by KR, which is a target site of Golgi protease, KexB, suggesting that AprA undergoes a similar proteolytic process to that known in the biosynthesis of ustiloxin B. 18 AprA is also modified by AprY and AprR to furnish 1. However, there is no information concerning the order of these posttranslational modifications.…”
mentioning
confidence: 99%
“…Upon further examination, the cluster gene ustA, was predicted to encode a protein containing an N-terminal signal sequence and 16-fold repeated peptide region containing YAIG repeats which represent the exact tetrapeptide sequence of ustiloxin B. Biosynthesis was proposed to proceed via processing of the UstA precursor protein by a Kex2 protease not present in the cluster that cleaves at nearby Lys-Arg residues on the C-terminal side of the YAIG tetrapeptide 17) . Subsequent work in A. oryzae confirmed that inactivation of the kexB endopeptidase gene resulted in almost complete loss of ustiloxin B 156) . The partially processed pre-protein is then believed to be processed in a stepwise manner by the products of ustP and ustH, both encoding peptidases, resulting in generation of the mature YAIG tetrapeptide.…”
Section: -6 Ustiloxin B Clustermentioning
confidence: 96%